PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KOTA TASIKMALAYA - Nida Nurul Pitroh; Hamdi Supriadi (CV. Denasya Smart Publisher, 2025)
The purpose of this study was to determine the effect of work discipline and physical work environment on employee performance at the Tasikmalaya City Environmental Service. The method used in this study is quantitaive. The sampling technique used the slovin technique and obtained a sample of 57 respondents. Data collection by distributing questionnaires to all respondents using the Likert scale as a measurement scale and SPSS version 25 as a data processing application. Data analysis used validity tests, reability test, classical assumption test, regression analysis, correlation coefficients, determination coefficients and hypothesis test. The results of this study are that Work Discipline has a significant effect on employee performance at the Tasikmalaya City Environmental Service, this can be proven from the simple linier regression equation Y = 25,253 + 0,403X1, a correlation value of 0,386 (has a low level of relationship). The coefficient of determination or contribution of its influemce is 14,9% and the hypothesis test obtained tcount > ttabel or (3,104 > 1,673). Partial hypothesis test of independent variables affects the dependent variable whit the decision Ho is rejected and H1 is accepted, meaning there is a significant influence. It is said to be significant because the probability significance value is 0,003 < 0,05. Physical Work Environment has a significant effect on employee performance at the Tasikmalaya City Environmental Service. This can be proven from the regression equation Y = 23,313 + 0,455X2, the correlation value is 0,501 (has a moderate level of relationship). The coefficient of determination or contribution of its influence is 25,1% and the hypothesis test obtained tcount > ttabel or (4,293 > 1,673). Partial hypothesis test of independent variables affects the dependent variable whit the decision Ho is rejected and H2 is accepted, meaning there is a significant influence. It is said to be significant because the probability significance value is 0,000 < 0,05. Work Discipline and Physical Work Environment simultaneously have a positive and significant at the Tasikmalaya City Environmental Service. This can proven from the regression equation Y = 9,436 + 0,358X1 + 0,426X2, a correlation value of 0,606 (having a strong relationship). The coefficient of determination or contribution of its influence is 36,8% and the hypothesis test obtained the value og Fcount > Ftabel or (15,702 > 3,17). Sumlatnaeous hypothesis testing of independent variables influences the dependeny variable whit decision H1 and H3 accepted, meaning there is a significant influence. It is said to be significant because the probability significance value < 0,05.